2020
DOI: 10.1088/1755-1315/454/1/012142
|View full text |Cite
|
Sign up to set email alerts
|

Application of biofertilizer consortium formulation of cellulolytic bacteria based on organic liquid waste on yield of upland rice (Oryza sativa L.)

Abstract: Rice production in Riau Province is lower than demand. One of the efforts made is the use of organic fertilizer based on organic liquid waste, in addition to reducing the use of inorganic fertilizers. The method that can be applied to support rice yield is the use of cellulolytic bacterial consortium applications. This study aimed to finding out the formulation and dose of biological fertilizer based on cellulolytic bacteria based on the organic liquid waste that was good for growth and yield of upland rice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…[8] reported that the application of several biofertilizer wastes did not have a significantly different effect on several growth and production parameters [9]. Also showed that the application of biofertilizer waste did not have a significantly different effect on the parameters of panicle length, number of pithy grains per panicle, 1000 grain weight, percentage of pithy grain, weight of milled dry grain per clump [10]. The application of biofertilizers on upland rice plants has not seen a real effect.…”
Section: Rice Plant Growthmentioning
confidence: 99%
“…[8] reported that the application of several biofertilizer wastes did not have a significantly different effect on several growth and production parameters [9]. Also showed that the application of biofertilizer waste did not have a significantly different effect on the parameters of panicle length, number of pithy grains per panicle, 1000 grain weight, percentage of pithy grain, weight of milled dry grain per clump [10]. The application of biofertilizers on upland rice plants has not seen a real effect.…”
Section: Rice Plant Growthmentioning
confidence: 99%
“…Tanaman yang tumbuh dengan baik karena nutrisinya terpenuhi belum tentu bebas dari serangan hama dan penyakit tumbuhan. Limbah cair tahu pada volume 15 ml dapat meningkatkan jumlah biji padi per malai, akan tetapi tanaman padi tersebut terancam oleh gangguan hama, berupa walangsangit dan kumbang lainnya, sehingga efek peningkatan jumlah biji per malainya tidak terlalu signifikan (Hapsoh, et al, 2019).…”
Section: Pendahuluanunclassified
“…The given cellulolytic bacterial consortium can also be applied in the form of biofertilizer. The biofertilizer has been applied to several plants, namely rice plants [6] and corn plants [7]. Some of the functions of biofertilizer are increasing the availability of essential macro nutrients (N, P and K) [8], producing phytohormones that can stimulate plant growth [9], NPK fertilizer can be reduced by 30%, and yields increase in horticultural crops.…”
Section: Introductionmentioning
confidence: 99%